Epidemiological investigation reveals genetic diversity and high co-infection rate of canine bocavirus strains circulating in Heilongjiang province, Northeast China. (June 2016) - Guo, Donghua; Wang, Zhihui; Yao, Shuang; Li, Chunqiu; Geng, Yufei; Wang, Enyu; Zhao, Xiwen; Su, Mingjun; Wei, Shan; Wang, Xinyu; Feng, Li; Chang, Yung-fu; et al.
Abstract: To trace evolution of CBoV in Northeast China, 201 fecal samples from rectal swabs of diarrheic dogs collected from May 2014 to April 2015 were investigated using PCR targeting partial NS1 gene (440 bp). Furthermore, phylogenetic analysis of the identified CBoV strains was conducted using nucleotide sequences of the partial NS1 gene. The results indicated that 15 of 201 fecal samples (7.5%) were positive for CBoV; the partial NS1 genes of the 15 CBoV strains exhibited 83.1%–100% nucleotide identity, and 75.8%–100% amino acid identity; the entire VP2 gene of five selected CBoV strains exhibited 82.9%–96.8% nucleotide identity, and 90.4%–99.1% amino acid identity. The 15 CBoV strains exhibited high co-infection rates with CPV-2 (40%), CCoV (20%), and CaKV (26.67%). Phylogenetic analysis of the partial NS1 gene revealed that the 15 CBoV strains were divided into different subgroups of CBoV-2 when compared with CBoV-2 strains from South Korea, USA, Germany, and Hong Kong in China. Moreover, phylogenetic analysis of the VP2 gene indicated that five selected CBoV strains were divided into three different genetic groups of CBoV-2, involving in CBoV-2HK group, CBoV-2C group, and CBoV-2B group. The recombination analysis using the entire VP2 gene revealed three potential recombination events that occurred among five selected strains in our study. These data demonstrated that the CBoV strains circulating in Heilongjiang province, Northeast China showed genetic diversities, potential recombination events, and high co-infection rate. Further studies will be required to address the potential pathogenic role of these diverse CBoV strains. Highlights: Canine bocavirus (CBoV) exhibits high prevalence in Northeast China from 2.8% to 20%. We revealed high co-infection of CBoV with canine parvovirus-2, canine coronavirus, and canine kobuvirus. The CBoV strains circulating in Northeast China show multiple genetic groups. Potential recombination events occur among the CBoV strains circulating in Northeast China.